2013
DOI: 10.1128/jvi.02516-12
|View full text |Cite
|
Sign up to set email alerts
|

Integrin and Defensin Modulate the Mechanical Properties of Adenovirus

Abstract: The propensity for capsid disassembly and uncoating of human adenovirus is modulated by interactions with host cell molecules like integrins and alpha defensins. Here, we use atomic force microscopy (AFM) nanoindentation to elucidate, at the single-particle level, the mechanism by which binding of these host molecules affects virus particle elasticity. Our results demonstrate the direct link between integrin or defensin binding and the mechanical properties of the virus. We show that the structure and geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 50 publications
8
78
1
2
Order By: Relevance
“…HD5-treated virions that did colocalize to the ER showed no evidence of VP2 exposure, suggesting that HD5 may also stabilize virions that do the reach the ER from host cell chaperones that drive the unfolding reaction. There is precedent in the literature for this, as other viruses have been shown to be stabilized by alpha defensins (29,47).…”
Section: Hd5 Does Not Neutralize Jcpyv Infection By Blocking Internalmentioning
confidence: 99%
“…HD5-treated virions that did colocalize to the ER showed no evidence of VP2 exposure, suggesting that HD5 may also stabilize virions that do the reach the ER from host cell chaperones that drive the unfolding reaction. There is precedent in the literature for this, as other viruses have been shown to be stabilized by alpha defensins (29,47).…”
Section: Hd5 Does Not Neutralize Jcpyv Infection By Blocking Internalmentioning
confidence: 99%
“…Interestingly, the stiffness of icosahedral viral capsids is reinforced anisotropically: for example, with the least enforcement at the 5-fold and the strongest enforcement at the 2-fold symmetry axis. Accordingly, the elastic properties of the penton region around the 5-fold symmetry axis of adenovirus are modulated by host factors, such as integrins and defensins, which play important roles in virus disassembly in cells (7,8). This evidence highlights the importance of capsid mechanics and how host interactions tune viral mechanics.…”
Section: Virus Mechanics Are Key For Infectionmentioning
confidence: 92%
“…Cells adhere to a substrate through their integrins, which link with the cytoskeleton to regulate the mechanical properties of cells (Snijder et al 2013;Mierke 2013;Schoen et al 2013;Yamahashi et al 2015). The results of the AFM measurements on cells growing on different films indicated that the average Young's modulus of cells growing on the 10 % PEGDA-PS hydrogel was 0.62 ± 0.02 kPa, while that of cells growing on the 50 % PEGDA-PS hydrogel was higher, at 1.01 ± 0.05 kPa (Fig.…”
Section: Effect Of Ps On Mechanical Properties Of Hydrogelsmentioning
confidence: 99%